Kooperation und Innovation im Speyerer Buchdruck des ausgehenden Mittelalters - Schweitzer-Martin, Paul (Materiale Textkulturen, 2022)
This study examines Speyer, a significant medieval printing location, where four printers operated between 1471 and 1500. Alongside the most important workshop belonging to the Drach family, the brothers Johann and Conrad Hist printed there, as did two anonymous printing firms. This volume builds on their biographies to examine and compare their respective incunabulum production in terms of its content, design, use of paper, and dissemination.